Identifying with Our Desires. (6th February 2013) - Miller, Christian
Abstract A number of philosophers have become convinced that the best way of trying to understand human agency is by arriving at an account of identification. My goal here is not to criticize particular views about identification, but rather to examine several assumptions which have been widely held in the literature and yet which, in my view, render implausible any account of identification that takes them on board. In particular, I argue that typically identification does not involve either reflective consideration of our mental states or endorsement of those states. If it did, we would rarely be agents.